A Sustainable Development-Driven Framework: Aligning Agricultural Environmental Impact Assessment with the 2030 Agenda - Viriato, Viviany [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Nunes, Marcio Renato (Springer Nature, 2025)
Impacts of agriculture are commonly assessed using farm-level tools, especially when the primary objective is to provide environmental management advice on technology adoption and production practices. Among these tools, Ambitec-Agro, developed in 2003 based on the Environmental Impact Assessment (EIA) framework, has been widely applied to evaluate the socioenvironmental performance of agricultural technologies in a cost-effective and efficient manner. In light of new international governance commitments related to the United Nations Sustainable Development Goals (SDGs), this manuscript presents the updated version of Ambitec-Agro and its alignment with the 2030 Agenda for Sustainable Development focused on crop production. A qualitative, descriptive, and exploratory methodology was adopted, including the selection of relevant SDGs and the revision of the tool’s indicators through document analysis, expert consultation, and literature review. The original tool comprises 2 dimensions, 7 aspects, 27 criteria, and 148 indicators. The updated version maintains the original structure and core principles but includes 25 criteria and 139 indicators. A total of 66 indicators were revised: 18 were removed, 14 added, 2 reallocated across criteria, 22 modified, and 10 merged into 5. These revisions enhance the tool’s relevance, coherence, and applicability for evaluating agricultural technologies in the context of contemporary sustainability priorities.